Systematic review of battery cooling technologies in electric vehicles: Methods, challenges, and recent innovations - Priyadi, Muhammad Untung Zaenal; Gamayel, Adhes; Chandrasa, Ganesha Tri; Priandana, Eka Rakhman; Nugraha, Heri; Haq, Imaduddin; Kurniawan, Panca (Universitas Muhammadiyah Magelang, 2025)
This study presents a comprehensive review of battery cooling technologies in electric vehicles (EVs), focusing on their effectiveness, challenges, and recent innovations. The research methodology involved analyzing various cooling methods, including air cooling, liquid cooling, phase change materials (PCM), and thermoelectric cooling systems, through a systematic literature review. The study evaluated these technologies based on their thermal efficiency, design complexity, implementation costs, and performance across different environmental conditions. The findings reveal that while air cooling offers simplicity and cost-effectiveness, it demonstrates limited thermal efficiency for high-performance applications. Liquid cooling systems, despite higher complexity and costs, provide superior thermal management, maintaining battery temperatures within optimal ranges. PCM-based systems effectively manage short-term heat spikes but face limitations in thermal conductivity and long-term stability. Hybrid cooling solutions, particularly those combining PCM with liquid cooling, showed significant improvements in thermal efficiency, achieving temperature reductions of 40-50 °C compared to conventional methods. The integration of nanotechnology, specifically through nanofluids and graphene-based materials, enhanced heat transfer efficiency by 20-30%. The study concludes that future developments in EV battery cooling systems will increasingly integrate artificial intelligence and smart technologies for adaptive thermal management, while hybrid cooling solutions emerge as the most promising approach for optimizing battery performance and longevity. These advancements are crucial for the continued evolution of electric vehicle technology and sustainable transportation solutions.